To Teach the Body What Is Not Good: Time, Space, and Embodiment in Religious Treatment for Drug Addiction - Olivas Hernández, Olga Lidia (Journal for the scientific study of religion, 2025)
From a cultural phenomenology approach, this paper analyzes the experiences of spiritual warfare lived in an Evangelical Rehabilitation Center. The ethnographic study was conducted in Tijuana, B.C., Mexico. The discussion focuses on three paradigmatic cases, allowing us to analyze the transition from “life in addiction” to the experience of transforming desires, which also implies a process of subjectivity. We argue that desire is a bodily phenomenon with palpable somatic manifestations. However, in an existential sense, desire is also the corporeal link between spatiality and temporality. We maintain that the corporeal subjectivity of addiction defines spatiality and temporality in a way that is particularly susceptible to formulation in religious discourse, leading to a transformative shift in orientational self-processes of being in the world, where an existential struggle becomes spiritual warfare, simultaneously on the scale of embodiment and in a cosmic struggle between good and evil.